Congenital Coronary Artery Anomalies: Three Cases and Brief Review of the Literature - Ioakeimidis, Nikolaos S. (Case Rep Vasc Med, 2021)
Coronary artery anomalies (CAAs) are congenital vascular defects which can remain hidden and asymptomatic over the complete life course of an individual. They are defined as deviations from the normal coronary anatomy regarding the arterial origin, course, or both. Their incidence varies from 1.3% to 5.64% in coronary angiography cohorts, and they can be detected as incidental findings. In certain cases, CAAs can be hemodynamically significant and unfortunately can be proven lethal. Their link with sudden cardiac death, especially in otherwise healthy competitive athletes, is well established, but their prognostic significance, range of symptoms, and pathophysiology remain to be further elucidated. Here, along with a brief review of related literature, we present a series of three cases: one case of an anomalous origin of the right coronary artery (RCA) from the left coronary sinus, one case of a split RCA originating from the left coronary sinus, and one case of a dual left anterior descending (LAD) artery system.